THE EFFECT OF SERVANT LEADERSHIP, ORGANIZATIONAL CULTURE IN EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION ( STUDY CASE OF AL-KAHFI ISLAMIC BOARDING SCHOOL, SOMALANGUN, KEBUMEN) - Muhammad Azim; Muafi Muafi (Proceedings on Engineering Sciences, 2019)
The purpose of this research is to examine the effect of servant leadership and organizational culture on employee performance mediated by job satisfaction (the study case on employee al-kahfi Islamic boarding school somalangu, kebumen). This research uses quantitative approach, data collected from 100 respondents which are the employee of al-kahfi Islamic boarding school somalagu,kebumen. The SmartPLS30 is used as tool of analysis with SEM analysis method (Structural Equation Modeling). The results of this research show that servant leadership had positive effect and significant on job satisfaction and servant leadership doesn’t affect on the employee performance. Organizational culture had positive effect and significant on the employee performance and job satisfaction. Job satisfaction had positive relationship and significant on employee performance, job satisfaction mediate relationship between servant leadership and employee performance,job satisfaction mediate relationship between organizational culture and employee performance.